Role of proline and pyrroline-5-carboxylate metabolism in plant defense against invading pathogens - Qamar, Aarzoo; Mysore, Kirankumar; Senthil-Kumar, Muthappa (Frontiers in Plant Science, 2015)
Pyrroline-5-carboxylate (P5C) is an intermediate product of both proline biosynthesis and catabolism. Recent evidences indicate that proline-P5C metabolism is tightly regulated in plants, especially during pathogen infection and abiotic stress. However, role of P5C and its metabolism in plants has not yet been fully understood. Studies indicate that P5C synthesized in mitochondria has a role in both resistance (R)-gene-mediated and nonhost resistance against invading pathogens. Proline dehydrogenase (ProDH) and delta-ornithine amino transferase (δOAT)-encoding genes, both involved in P5C synthesis in mitochondria are implicated in defense response of Nicotiana benthamiana and Arabidopsis thaliana against bacterial pathogens. Such defense response is proposed to involve salicylic acid-dependent pathway, reactive oxygen species (ROS) and hypersensitive response (HR)-associated cell death. Recently HR, a form of programmed cell death (PCD), has been proposed to be induced by changes in mitochondrial P5C synthesis or the increase in P5C levels per se in plants inoculated with either a host pathogen carrying suitable avirulent (Avr) gene or a nonhost pathogen. Consistently, A. thaliana mutant plants deficient in P5C catabolism showed HR like cell death when grown in external P5C or proline supplemented medium. Similarly, yeast and plant cells under oxidative stress were shown to increase ROS production and PCD due to increase in P5C levels. Similar mechanism has also been reported as one of the triggers for apoptosis in mammalian cells. This review critically analyzes results from various studies and enumerates the pathways for regulation of P5C levels in the plant cell, especially in mitochondria, during pathogen infection. Further, mechanisms regulating P5C- mediated defense responses, namely HR are outlined. This review also provides new insights into the differential role of proline-P5C metabolism in plants exposed to pathogen infection.